Targeting endosomal pH for cancer chemotherapy - Fabrice Lucien; Roxane R. Lavoie; Claire M. Dubois (Molecular & Cellular Oncology, 2018)
Altered pH homeostasis in cancer cells has been linked with essentially all classical hallmarks of cancer, including chemoresistance. We recently identified a conceptually novel mechanism for how dysregulated pH in hypoxic cells causes chemoresistance which is based on the aberrant cellular distribution of the endosomal pH regulator, the sodium/hydrogen exchanger 6 (NHE6).